Cefiderocol susceptibility of Stenotrophomonas maltophilia species complex and carbapenem-resistant Pseudomonas aeruginosa isolates from blood cultures at a university hospital in Tokyo, Japan - Wataru Aoki; Yoshifumi Uwamino; Nagi Niida; Hiroaki Kubota; Yuka Kamoshita; Rika Inose; Mika Nagata; Osamu Ishihara; Shunsuke Uno; Ayumi Yoshifuji; Ho Namkoong; Naoki Hasegawa; et al. (Journal of Global Antimicrobial Resistance)
Objective: Cefiderocol, a siderophore cephalosporin, has shown promise against carbapenem-resistant strains such as Pseudomonas aeruginosa and Stenotrophomonas maltophilia species complex. Despite its recent approval in Japan, susceptibility data remain limited. Therefore, this study evaluated the cefiderocol susceptibility of carbapenem-resistant P. aeruginosa and S. maltophilia species complex strains isolated from blood cultures to determine whether cefiderocol can be used as an empirical treatment option. Methods: Carbapenem-resistant P. aeruginosa and S. maltophilia species complex strains isolated from blood cultures at a university hospital in Japan were included. Minimum inhibitory concentrations (MICs) and inhibition zone diameters were assessed using broth microdilution and disk diffusion methods, respectively. Whole-genome sequencing was conducted to elucidate the genetic backgrounds of the clinical isolates. Results: The MIC50 and MIC90 values for cefiderocol in 65 carbapenem-resistant P. aeruginosa strains were 0.12 and 0.25 µg/mL, and 0.06 and 0.25 µg/mL for 51 S. maltophilia species complex strains, respectively. One S. maltophilia species complex strain exhibited non-susceptibility, with a MIC of 2 µg/mL in broth microdilution, while disk diffusion methods demonstrated susceptibility. A significant negative correlation was observed between MIC values and inhibition zone diameters. Whole-genome sequencing revealed that a limited number of P. aeruginosa strains possessed carbapenemase genes. Conclusions: The findings of this study support the efficacy of cefiderocol against carbapenem-resistant P. aeruginosa and S. maltophilia species complex, suggesting its potential as an empirical treatment option for bloodstream infection patients in Japan. Continued surveillance is advised to monitor resistance trends with increased cefiderocol use.